Using internal communication for brand building. The MMI Holdings Limited case study - Booysen, Tosca (The IIE, 2017)
MMI Holdings Limited (MMI) is a South African based financial services group listed on the Johannesburg Stock Exchange (JSE). MMI was established from the merger of Metropolitan and Momentum, both are South African based insurance-based financial services companies. In 2010, at the time of the merger MMI was positioned as an investor brand; however in 2016 it was repositioned as a client facing brand without a clearly communicated brand strategy to employees. Organisations place more emphasis on building their brands externally. Brand building starts with employees. It is as important for organisations to build their brand internally, as they do externally. Based on this notion the main objective of the study was to explore and describe how internal communication is used or brand building at MMI. The goal was to find out how internal communication is used as a strategy for brand building within organisations. This study uses of a mixed method approach, this includes using both quantitative and qualitative approaches. The data collection method used was an online survey and face-to-face interviews with MMI employees. The objectives of the study was to investigate internal communication strategies, explore the relationship between internal communication and brand building, and describe the existing brand identity symbols used by internal communication for brand building. Findings identified a need to increased leadership and HR driven brand buildings initiatives and confirmed the need for the brand strategy to be communicated.
Keywords: Financial Services; Brand Building, Financial Services; Brand Building; Brand Communication Strategy; Brand Identity